Chemical hydrodynamics of a downward microbubble flow for intensification of gas‐fed bioreactors. Issue 4 (27th October 2017) - Ansari, Manizheh; Turney, Damon E.; Yakobov, Roman; Kalaga, Dinesh V.; Kleinbart, Simon; Banerjee, Sanjoy; Joshi, Jyeshtharaj B.
Abstract : Bioreactors are of interest for value‐upgrading of stranded or waste industrial gases. Reactor intensification requires development of low cost bioreactors with fast gas–liquid mass transfer rate. Here we assess published reactor technology in comparison with a novel downward bubble flow created by a micro‐jet array. Compared to known technology, the advanced design achieves higher volumetric gas transfer efficiency (kL a per power density) and can operate at higher kL a. We measure the effect of four reactor heights (height‐to‐diameter ratios of 12, 9, 6, and 3) on the gas transfer coefficient kL, total interfacial area a, liquid residence time distribution, energy consumption, and turbulent hydrodynamics. Leading models for predicting kL and a are appraised with experimental data. The results show kL is governed by "entrance effects" due to Higbie penetration dominate at short distances below the micro‐jet array, while turbulence dominates at intermediate distances, and finally terminal rise velocity dominates at large distances. © 2017 American Institute of Chemical Engineers AIChE J, 64: 1399–1411, 2018